The selective peroxisome proliferator-activated receptor alpha modulator (SPPARMα) paradigm: conceptual framework and therapeutic potential : A consensus statement from the International Atherosclerosis Society (IAS) and the Residual Risk Reduction Initiative (R3i) Foundation - Fruchart, Jean-Charles; Santos, Raul D; Aguilar-Salinas, Carlos; Aikawa, Masanori; Al Rasadi, Khalid; Amarenco, Pierre; Barter, Philip J; Ceska, Richard; Corsini, Alberto; Després, Jean-Pierre; Duriez, Patrick; Eckel, Robert H; et al. (Cardiovascular diabetology, 2019)
In the era of precision medicine, treatments that target specific modifiable characteristics of high-risk patients have the potential to lower further the residual risk of atherosclerotic cardiovascular events. Correction of atherogenic dyslipidemia, however, remains a major unmet clinical need. Elevated plasma triglycerides, with or without low levels of high-density lipoprotein cholesterol (HDL-C), offer a key modifiable component of this common dyslipidemia, especially in insulin resistant conditions such as type 2 diabetes mellitus. The development of selective peroxisome proliferator-activated receptor alpha modulators (SPPARMα) offers an approach to address this treatment gap. This Joint Consensus Panel appraised evidence for the first SPPARMα agonist and concluded that this agent represents a novel therapeutic class, distinct from fibrates, based on pharmacological activity, and, importantly, a safe hepatic and renal profile. The ongoing PROMINENT cardiovascular outcomes trial is testing in 10,000 patients with type 2 diabetes mellitus, elevated triglycerides, and low levels of HDL-C whether treatment with this SPPARMα agonist safely reduces residual cardiovascular risk.
Keywords: Animals; Benzoxazoles; hodnocení rizik; Remnant cholesterol; Visceral obesity; butyráty; biologické markery; Biomarkers; Selective peroxisome proliferator-activated receptor alpha modulator; Dyslipidemias; Atherogenic dyslipidemia; výsledek terapie; PPAR alpha; lipidy; Triglycerides; cílená molekulární terapie; lidé; Butyrates; Residual cardiovascular risk; konsensus; signální transdukce; Lipids; Treatment Outcome; bezpečnost pacientů; Risk Assessment; PPAR alfa; Signal Transduction; Inflammation; PROMINENT; Consensus; Risk Factors; Pemafibrate (K-877); SPPARMalpha; Hypolipidemic Agents; Cardiovascular Diseases; benzoxazoly; Diabetes; hypolipidemika; dyslipidemie; rizikové faktory; kardiovaskulární nemoci; zvířata; Molecular Targeted Therapy; Patient Safety; Humans